2022
DOI: 10.1002/ente.202200014
|View full text |Cite
|
Sign up to set email alerts
|

A Triboelectric Piston–Cylinder Assembly with Condition‐Monitoring and Self‐Powering Capabilities

Abstract: The condition monitoring of piston–cylinder‐reciprocating machinery usually relies on vibration and acoustic sensors installed on the outer surface of cylinders. However, vibration and acoustic signals are susceptible to external interference from other accessories, and require an external power supply, which limits its widespread application. Herein, based on the lateral sliding mode of triboelectric nanogenerator (TENG), a novel reciprocating device with condition‐monitoring and self‐powering capabilities is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Kokjohn et al, (2011) showed that ignition timing and combustion rate can be controlled by varying the proportions of each fuel and was able to achieve an indicated thermal efficiency of 53% with negligible NOx and soot. It was also reported that flame propagation did not play a significant role due to presence of very lean mixtures during the start of combustion and that the combustion rate is controlled through chemical kinetics like in HCCI (Zhao, et al, 2020;Iqbal, et al, 2020;Li, et al, 2022;Wu, et al, 2019;Adzuan, & Yusop, 2022;Rangasamy, et al, 2020). Comparatively, Figure 2 shows the various LRF delivery methods; conventional premixed port injection, dual direct injection, and the proposed port injection at the valve for this research.…”
Section: Figure 1 Schematic Of Rcci Combustion Strategymentioning
confidence: 97%
“…Kokjohn et al, (2011) showed that ignition timing and combustion rate can be controlled by varying the proportions of each fuel and was able to achieve an indicated thermal efficiency of 53% with negligible NOx and soot. It was also reported that flame propagation did not play a significant role due to presence of very lean mixtures during the start of combustion and that the combustion rate is controlled through chemical kinetics like in HCCI (Zhao, et al, 2020;Iqbal, et al, 2020;Li, et al, 2022;Wu, et al, 2019;Adzuan, & Yusop, 2022;Rangasamy, et al, 2020). Comparatively, Figure 2 shows the various LRF delivery methods; conventional premixed port injection, dual direct injection, and the proposed port injection at the valve for this research.…”
Section: Figure 1 Schematic Of Rcci Combustion Strategymentioning
confidence: 97%